2012
DOI: 10.5772/50527
|View full text |Cite
|
Sign up to set email alerts
|

Methodology to Optimize Manufacturing Time for a CNC Using a High Performance Implementation of ACO

Abstract: In this paper, an efficient methodology to generate optimal and/or quasi-optimal sequences of G commands to minimize the manufacturing time is presented. Our solution starts from original G codes provided by application CAD/CAM software. Here, first we tackled the problem of reducing the time of the travel path for drilling of an industrial robotic manufacturing machine. The methodology can be easily implemented for free distribution or commercial CAD/CAM software without achieving any modification to it. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In M1, the cost of the tour started at 1100mm and ended at 4117mm after a total of 108 iterations. In M2, the cost of the tour started at 7750mm and ended at 4900mm.The optimized cost of the tour for the omega plate problem is 4117mm and the optimal sequence by using proposed hybrid algorithm is [1,2,3,4,5,6,7,8,13,18,17,14,15,16,25,24,23,22,21,20,19,12,11,10,9, and 1], which has been obtained through memeplex 2 (M2).…”
Section: B Formulation Of Problem and Results Obtainedmentioning
confidence: 99%
See 1 more Smart Citation
“…In M1, the cost of the tour started at 1100mm and ended at 4117mm after a total of 108 iterations. In M2, the cost of the tour started at 7750mm and ended at 4900mm.The optimized cost of the tour for the omega plate problem is 4117mm and the optimal sequence by using proposed hybrid algorithm is [1,2,3,4,5,6,7,8,13,18,17,14,15,16,25,24,23,22,21,20,19,12,11,10,9, and 1], which has been obtained through memeplex 2 (M2).…”
Section: B Formulation Of Problem and Results Obtainedmentioning
confidence: 99%
“…The results achieved are compared with the results of MasterCAM and it is found that drilling time achieved by ACO is less than the time taken by MasterCAM in all case studies. ACO metaheuristic was also applied in [3] for optimization of circular pattern drilling problems. ACO results are compared with the results of MasterCAM and the improvement in the results achieved by ACO is around 62.27%.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed literature review on HDPOP is presented by Dewil et al [9] and Abidin et al [10], in which various heuristic approaches proposed to solve HDPOP are listed. Considering both single and multi-tool hole drilling path optimization problems, well-known simulated annealing algorithm [12], tabu search algorithm [13] ant colony optimization algorithm [11,14,15], particle swarm optimization algorithm [16][17][18], genetic algorithm [19][20][21][22][23] are proposed. In addition to these algorithms, various recent algorithms are also implemented to HDPOP, such as biogeography based optimization [24], charged system search algorithm [25], hybrid cuckoo search-genetic algorithm [26], shuffled frog leaping algorithm [18], optimal foraging algorithm [27], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Many types of techniques, including a hybrid GA (Gupta et al, 2011), parallel ant colony (Montiel-Ross et al, 2012), and hybrid ant colony together with a GA (Abbas et al, 2014), have been used in previous studies. Research on path optimization has been inspired by not only biological phenomena but also physical phenomena.…”
Section: Introductionmentioning
confidence: 99%